New developments in gold-catalyzed manipulation of inactivated alkenes - Chiarucci, Michel; Bandini, Marco (Beilstein Journal of Organic Chemistry, 2013)
Over the recent years, the nucleophilic manipulation of inactivated carbon–carbon double bonds has gained remarkable credit in the chemical community. As a matter of fact, despite lower reactivity with respect to alkynyl and allenyl counterparts, chemical functionalization of isolated alkenes, via carbon- as well as hetero atom-based nucleophiles, would provide direct access to theoretically unlimited added value of molecular motifs. In this context, homogenous [Au(I)] and [Au(III)] catalysis continues to inspire developments within organic synthesis, providing reliable responses to this interrogative, by combining crucial aspects such as chemical selectivity/efficiency with mild reaction parameters. This review intends to summarize the recent progresses in the field, with particular emphasis on mechanistic details.
Keywords: alkene; gold catalysis; mechanism; organic synthesis